1991
DOI: 10.1016/1010-7940(91)90040-q
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality treatment for small cell bronchial carcinoma *1, *2Preliminary results of a prospective, multicenter trial

Abstract: Preliminary results of the 1984 ISC (International Society of Chemotherapy) lung cancer studies I and II as of June 1990 are based on 146 patients with small cell bronchial carcinoma from 23 departments of thoracic surgery. All patients received surgery for cure in cTNM stages I and II followed by randomization for two different types of chemotherapy. For disease-free patients after completion of postoperative chemotherapy, prophylactic cranial irradiation (PCI) was administered. For the two different chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…Schreiber et al [14] indicated that the use of surgery, particularly lobectomy, was associated with favorable survival outcomes. There were other reports regarding the surgical outcome using adjuvant therapies [1,15-17]. In these reports, in the majority of cases, the use of surgery as part of multimodality therapy had more successful outcomes than those of conventional therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Schreiber et al [14] indicated that the use of surgery, particularly lobectomy, was associated with favorable survival outcomes. There were other reports regarding the surgical outcome using adjuvant therapies [1,15-17]. In these reports, in the majority of cases, the use of surgery as part of multimodality therapy had more successful outcomes than those of conventional therapies.…”
Section: Discussionmentioning
confidence: 99%
“…19 Several authors have reported that a small minority of limited-stage SCLCs could be managed with an operation and postoperative chemotherapy. [1][2][3][4][5][6][7][8][9] According to those reports, the 5-year survivals were 28% to 36% overall and 26% to 61% in patients with stage I disease. However, most of those reports were retrospective and used various combinations of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Indications for surgical resection for SCLC have not yet been determined, although several authors have reported that a small minority of patients with limited-stage disease and adequate lung function might benefit from surgical resection. [1][2][3][4][5][6][7][8][9] According to these reports, the prognosis of resected SCLC was not so poor, especially when no pathologic nodal involvement was observed. The 5-year survival ranged from 26% to 61% in these trials if the tumor was stage I.…”
mentioning
confidence: 99%
“…Even after three to four chemotherapy cycles a rate of vital residual disease at the primary site between 55 and 80% has been found at adjuvant surgery (Shepherd et al, 1996). Interestingly, some of the resected specimens demonstrate a change to NSCLC-histopathologies -whether treatment induced or simply a result of initial tumour cell heterogeneity is still not clear (Shepherd et al, 1988 have given chemotherapy preoperatively to stages I-IIIA (Shepherd et al, 1989;Zatopek et al, 1991;Müller et al, 1992), others post-operatively (Macchiarini et al, 1989;Ulsperger et al, 1991;Davis et al, 1993). Modern cisplatin-based chemotherapy was rarely used and different policies concerning integration of radiotherapy were chosen.…”
Section: Discussionmentioning
confidence: 99%